2014
DOI: 10.1242/dev.097444
|View full text |Cite
|
Sign up to set email alerts
|

WOX13-like genes are required for reprogramming of leaf and protoplast cells into stem cells in the moss Physcomitrella patens

Abstract: Many differentiated plant cells can dedifferentiate into stem cells, reflecting the remarkable developmental plasticity of plants. In the moss Physcomitrella patens, cells at the wound margin of detached leaves become reprogrammed into stem cells. Here, we report that two paralogous P. patens WUSCHEL-related homeobox 13-like (PpWOX13L) genes, homologs of stem cell regulators in flowering plants, are transiently upregulated and required for the initiation of cell growth during stem cell formation. Concordantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 65 publications
(110 reference statements)
3
117
0
2
Order By: Relevance
“…P. patens WUSCHEL-related homeobox 13-like (PpWOX13) genes, homologs of stem cell regulators in flowering plants, were transiently up-regulated during moss stem cell formation. PpWOX13 genes were found upregulated during stem cell formation in detached leaves (Sakakibara et al 2014). We found that AhWOX13A and AhWOX13B expressed strongly in peanut root and were upregulated in RAM enriched region compared with root without RAM.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…P. patens WUSCHEL-related homeobox 13-like (PpWOX13) genes, homologs of stem cell regulators in flowering plants, were transiently up-regulated during moss stem cell formation. PpWOX13 genes were found upregulated during stem cell formation in detached leaves (Sakakibara et al 2014). We found that AhWOX13A and AhWOX13B expressed strongly in peanut root and were upregulated in RAM enriched region compared with root without RAM.…”
Section: Discussionmentioning
confidence: 67%
“…Only the members of the ancient/basal clade had a motif of 41 aa which contained the N-terminal domain (Sakakibara et al 2014), we named it ancient/basal motif. Ancient/basal motif was located in the N-terminal region of the HD domain ( Fig.…”
Section: Phylogenetic and Conservation Motifs Analyses Of Wox Family mentioning
confidence: 99%
“…Scale bars: a 6 μm, b 50 μm, c 1 mm, d 500 μm, e 200 μm, f 100 μm This high regeneration capacity also supports the cultivation of moss tissue in liquid medium using weekly disruption cycles and the easy regeneration of plants from protoplasts. The molecular mechanisms underlying this pluripotency have been investigated and unraveled several key players including a basic helix loop helix transcription factor and two WUSCHEL-related homeobox 13-like genes (Busch et al 2013;Nishiyama et al 2012;Sakakibara et al 2014). …”
Section: Mosses Are Haploid Dominantmentioning
confidence: 99%
“…In many plants, including Arabidopsis thaliana, Fucus (brown algae), Physcomitrella patens (moss), or rice (Brawley et al 1977;He et al 2007;Sato et al 2010;Sakakibara et al 2014), the zygote divides asymmetrically. In Arabidopsis, this division yields a small apical daughter cell that forms the embryo and a large basal daughter cell that will give rise mostly to the extraembryonic suspensor (Mansfield and Briarty 1991).…”
mentioning
confidence: 99%